Nickel complexes based on BIAN ligands: transformation and catalysis on ethylene polymerization. Issue 21 (7th May 2021) - Xu, Shuyun; Chen, Xuemeng; Luo, Gen; Gao, Wei
Abstract : Several nickel complexes bearing one or two bis(arylimino)acenaphthene ligands were prepared and well characterized. These nickel complexes were tested as catalysts for ethylene polymerization. Abstract : Treatment of bis(arylimino)acenaphthene ( Ar BIAN) with Ni(COD)2 in toluene afforded dmp BIANNi(COD) (2a, dmp = 2, 6-Me2 C6 H3 ) and dipp BIANNi(COD) (2b, dipp = 2, 6- i PrC6 H3 ), respectively, in moderate yields. Complexes 2a and 2b can be oxidized by a small amount of oxygen at low temperature leading to oxygen-bridged dinuclear Ni(ii ) complexes ( dmp BIANNi)2 (μ-O)2 (4a ) and ( dipp BIANNi)2 (μ-O)2 (4b ), respectively, as a purple powder. The reaction of Ar BIAN with 0.5 equiv of Ni(COD)2 or Ni(Ph3 P)4 gave bisligated complexes ( dmp BIAN)2 Ni (3a ) and ( dipp BIAN)2 Ni (3b ), which can be considered as Ni(0) complexes supported by two neutral BIAN ligands. Oxidation of the bisligated nickel complexes 3a and 3b with [Cp2 Fe][B(C6 F5 )4 ] afforded cationic Ni(i ) complexes [( dmp BIAN)2 Ni][B(C6 F5 )4 ] (5a ) and [( dipp BIAN)2 Ni][B(C6 F5 )4 ] (5b ), respectively, in which the Ni(i ) centre is chelated by two neutral Ar-BIAN ligands. These complexes were characterized by NMR and IR spectroscopy and DFT calculation, and the molecular structures of 3b, 4b, and 5b were well established by X-ray diffraction analysis. These complexes were evaluated as catalysts for ethylene polymerization in which 2b showed high activity in the presence of AlMe3 . 13 C NMR analysis of polymers showed that the 2b /AlMe3 catalytic system gave less-branched polymers when compared to that obtained with dipp BIANNiBr2 under the same conditions.